Constraint-Induced Aphasia Therapy in the Acute Stage: What Is the Key Factor for Efficacy? A Randomized Controlled Study. (January 2017) - Woldag, Hartwig; Voigt, Nancy; Bley, Maria; Hummelsheim, Horst
Background. Constraint-induced aphasia therapy (CIAT) has proven effective in patients with subacute and chronic forms of aphasia. It has remained unclear, however, whether intensity of therapy or constraint is the relevant factor. Data about intensive speech and language therapy (SLT) are conflicting. Objective. To identify the effective component of CIAT and assess the feasibility of SLT in the acute stage after stroke. Method. A total of 60 patients with aphasia (68.2 ± 11.7 years) were enrolled 18.9 days after first-ever stroke. They were randomly distributed into 3 groups: (1) CIAT group receiving therapy for 3 hours per day (10 workdays, total 30 hours); (2) conventional communication treatment group, with same intensity without constraints; and (3) control group receiving individual therapy twice a day as well as group therapy (total 14 hours). Patients were assessed pretreatment and posttreatment using the Aachener Aphasia Test (primary end point: token test) and the Communicative Activity Log (CAL). Results. Pretreatment, there were no between-group differences. Posttreatment, all groups showed significant improvements without between-group differences. Conclusion. It was found that 14 hours of aphasia therapy administered within 2 weeks as individual therapy, focusing on individual deficits, combined with group sessions has proven to be most efficient. This approach yielded the same outcome as 30 hours of group therapy, either in the form of CIAT or group therapy without constraints. SLT in an intensive treatment schedule is feasible and was well tolerated in the acute stage after stroke.